Post-Pandemic Scenarios of Economic Development of Developed Countries and Russia - L. A. Petrova; T. E. Kuznetsova; V. M. Volodin (Финансы: теория и практика)
Amid the Kondratiev cycle's downward slope movement and global pandemic, a recession in many countries is Likely to Lead to a deep long-term economic crisis. The aim of the article is to study the simplest recession indicators in developing and developed countries, economic-recovery measures, and economic development scenarios. The objectives of the paper are to study current economic situations in different countries, including Russia; identify measures to prevent a recession in developing and developed countries; evaluate possible economic development scenarios with regard to the cyclical dynamics in the current climate. The authors used methods of analysis, modelling, monitoring of major economic indicators based on the data of past recessions and other crises. The results of the research show different scenarios of economic growth depending on the number of Covid-19 cases and the effectiveness of government’s responses to the pandemic; a correlation between monetary and fiscal policies in overcoming crisis; monetary policy priorities necessary for economic recovery; problems and prospects of monetary and fiscal policy implementation. The authors concluded that GDP, unemployment, and inflation rate are key indicators for the evaluation of the current and future money, credit, and production-related events. Proactive measures ensure a smoother average economic growth. Both monetary and fiscal policy have advantages and disadvantages. Proactive measures, in particular, inevitably cause two time lags: in the reaction to a recession and in the effectiveness of implemented measures. The governments and central banks must be proactive in overcoming the economic recession and providing support to the citizens.